Teacher's Challenges in Teaching English to Young Learner using Montessori Method - Chong Kai Jian; Widi Syahtia Pane (Borneo Educational Journal (Borju), 2020)
Montessori Method is rarely used in Indonesia, especially Samarinda, and schools that apply this method are still relatively few. Teachers who choose this method and teach in schools that use this method are ready to face the challenges based on Pertiwi et al. (2020) when teaching children to learn English using a specific Method. This article reports a qualitative study that figures out the Teacher's challenges in teaching English for young learners around 5-6 years old using Montessori Method to "Follow the child" and use the English Language as their instruction language. Two kindergarten English teachers in Nido Montessori School participated in this study, and data were collected through interview-based on case study design. This study indicated that teachers face several challenges when teaching English to young learners using the Montessori Method. Children who lack the English Language create limited communication between teachers and children because children can express what they need using the Language. Children with different characteristics challenges teachers focus on each of them and follow all of their need. Teaching English to the young learner using Montessori Method sometimes does not match the teaching topic or lesson, and this challenging Teacher to quickly use another teaching technique to make all the children able to follow the lesson. In conclusion, teaching English to young learners using a specific method (Montessori Method) will challenge the English Teacher.